EVALUATION OF DIFFERENT SUBSTRATES ON THE ACCLIMATIZATION OF Epidendrum ibaguense KUNTH PLANTLETS - dos Santos, Maurício Reginaldo Alves; Smozinski, Caroline Vivian (Saber Científico (1982-792X), 2021)
The objective of this work was to evaluate the effectiveness of different substrates for the acclimatization of micropropagated plantlets of Epidendrum ibaguense orchid species. Plantlets cultivated in Knudson culture medium for two months were used, after development of leaves and rooting. The substrates were mature coconut fiber, pine bark, termite-house, sphagnum and charcoal, distributed in trays with 50 cells in randomized blocks, with three replications and 10 plantlets per plot. After 60 days, plant height and number of leaves were evaluated. The highest growth and increase in leaf number were observed using charcoal and pine bark. Termite-house and sphagnum resulted in low plantlet development probably due to high water retention. The use of charcoal and pine bark for acclimatization of plantlets of E. ibaguense is recommended.